Study of Post Harvest Changes in Fruit commodities : Banana and Orange (Storage and Packaging) - Sutrisno Adi Prayitno; Sugiyati Ningrum; Domas Galih Patria; Silvy Novita Antrisna Putri; Dwi Retnaningtas Utami; Rahmad Jumadi (Universitas Darussalam Gontor, 2023)
Ethylene compounds are used in the post-harvest handling of horticultural products to speed up the ripening process. Suitable storage and packaging would maintain the quality of horticultural products. Horticultural products undergo further metabolism evenafter harvesting such as transpiration, respiration, maturation, andripening. To prevent the rapid deterioration of horticultural produce (physical, nutritional, and sensory), postharvest handling requires proper ethylene dosing, proper packaging, and storage of the product during handling. The aim of this research was to observe and find out the effect of the ripening stage on bananas and how to package orange fruits on changes in quality during post-harvest storage. In this research using quantitativedescriptive data which only compares the test paramters with each treatment given. The results showed that there was an influence of ethylene compounds on the ripening process of bananas on sensory characteristics, the color changed from yellow to blackish brown, the aroma became more fragrant and the sweet taste became sweet and sour; increasing the value of total suspended solids (TSS) and decreasing the weight of bananas. Plastic packaging equipped with perforated holes also affects the quality of oranges, lower orange fruit weight loss, and better sensory characteristics in texture and color compared to oranges packaged in plastic without holes. Hence, the storage of oranges fruits in air-tight conditions is not recommended due to it can make CO2 to be trapped and accumulate in the packaging which can result in the formation of water droplets or dew that affect the quality of orange fruits